Cadmium sulphide nanoparticles from Cadmium (II) complex of (Cyclododecylidineamino)thiourea. Issue 1 (1st October 2022) - George, Jisha; Lekha, V S; Rathika Nath, G; Rajesh, K.
Abstract : Novel ligand (Cyclododecylidineamino)thiourea (CDDATU) and its Cadmium (II) complex were synthesized and characterized by IR, CHNS and Thermo gravimetric analysis.The complex was found to give highly crystalline, good quality, mono-dispersed Cadmium sulphide nanoparticles through polyol synthesis method using Glycerol as high boiling solvent. Characterization of Cadmium sulphide nanoparticles were done using SEM, EDX, TEM, UV, PL and PXRD studies.